FACTORS INFLUENCING ON ACCURACY OF MODELING OF METAL HEATING PROCESSES IN FURNACES - S. V. Korneev; P. E. Ratnikov; D. V. Mendelev (Литьë и металлургия)
It is shown that at modeling of metal heating processes in furnaces it is reasonable to determine source data in parameters, measurable and controllable in the operating process of aggregate.